Physicochemical, textural and structural characteristics of wheat gluten-soy protein composited meat analogues prepared with the mechanical elongation method. (April 2021) - Chiang, Jie Hong; Tay, Wesley; Ong, Dayna Shu Min; Liebl, David; Ng, Chee Peng; Henry, Christiani Jeyakumar
Graphical abstract: Highlights: Meat analogues were prepared by the mechanical elongation (ME) method. Striated texture was formed by highly compacted ultrathin filaments. Wheat gluten demonstrated potential in structuring meat analogues using ME method. Abstract: This study investigated the effect of mechanical elongation method by combining wheat gluten (WG) and soy protein isolate (SPI) (at the ratio of 100:0, 80:20, 60:40 and 40:60 % w/w dry protein basis), and studied the physicochemical, textural and structural characteristics of meat analogues (∼52 % moisture). The meat analogues were analysed and compared against commercial control samples of firm tofu, mock chicken, and steamed chicken. Meat analogues made with 100 %WG showed the lowest hardness and chewiness. Analysis of meat analogues by scanning electron microscopy (SEM) showed their unique compact ultrastructure which was distinct from the commercial control samples. However, the proportional concentration of WG had an insignificant impact on the ultrastructure. Increasing SPI concentrations improved lysine contents of meat analogues but were still significantly lower ( p< 0.05) than steamed chicken. The results from protein solubility analysis suggested that hydrogen bonds, disulphide bonds and hydrophobic interactions were the forces responsible for the formation, stabilisation and retention of the structures within the meat analogues. It was concluded that the use of WG and WG-SPI produced acceptable doughs that could be used for the development of meat analogues using the mechanical elongation method.